Studi Kasus Pria 71 Tahun dengan Pneumonia - Puspa Rosfadilla; Rifqa Sahirah (Lembaga Pengembangan Kinerja Dosen, 2025)
Pneumonia is a lung infection that causes inflammation in the lung parenchyma. Pneumonia is the third leading cause of death globally. In Indonesia, in 2018, the prevalence of pneumonia among all age groups reached 2.21%. This case report was obtained from primary data through anamnesis, physical examination, and supporting tests. The patient complained of shortness of breath. The shortness of breath occurred during moderate physical activity and improved with rest. The shortness of breath was not affected by the weather. The patient also complained of left chest pain, productive cough, fever, diarrhea, and weakness. Upon physical examination, the general status showed vesicular breath sounds and rhonchi in the left lung field. Chest X-ray revealed diffuse consolidation in the bilateral paracardial pulmonary areas, suggesting pneumonia. Laboratory tests showed elevated white blood cell count. The patient was given pharmacological and non-pharmacological management in the form of respiratory fluoroquinolone.